Understanding of antibiotic use and resistance among final-year pharmacy and medical students: a pilot study - Jamshed, Shazia Qasim; Elkalmi, Ramadan Mohamed Mahmod; Rajiah, Kingston; Mohammed Ahmed, Abdul Kareem; Shamsudin, Siti Hadijah; Siddiqui, Mohammad Jamshed Ahmad; Abdul Aziz, Mohamad Akram; Hanafi, Muhammad Badrulsyam; Mohammad Shariff, Najwa Izzati; Ramlan, Nasrul Hakim; Jamil, Normunirah; Mustapha, Nur Hayatul Akmal; et al. (Open Learning on Enteric Pathogens, 2014)
Introduction: This study is aimed to investigate the understanding of antibiotic use and antibiotic resistance and its correlate factors among final-year medical and pharmacy students at International Islamic University Malaysia (IIUM). Methodology: This was a cross-sectional study. The study instrument was developed by extensive literature search and was subjected to face validity and content validity to medical and pharmacy academics. A pilot study was conducted to ascertain the reliability coefficient. Data was entered to SPSS version 17 and descriptive and inferential statistics were applied. Results: A total of 123 questionnaires were included in the study. Out of 123 respondents, 58.5% (n = 72) were final-year medical students, while 41.5% (n = 51) were final-year pharmacy students. The majority of the respondents showed adequate knowledge regarding the course contents related to antibiotics (n = 116; 94.3%). Almost all the respondents correctly reported the difference between bactericidal and bacteriostatic antibiotics. Only 15.4% (n = 19) and 27.6% (n = 34) of students were able to recognize Streptococcus pyogenes as non-pencillin resistant bacterium and Enterococcus as vancomycin-resistant bacterium, respectively. Conclusions: The students showed good understanding regarding antibiotic resistance. In comparison to medical students, pharmacy students showed better understanding and more adequate knowledge, as the mean value for each domain was slightly higher for pharmacy students. Extensively improving the curriculum and educating healthcare professionals, especially physicians and pharmacists, right from the time of their educational training can inculcate a moral responsibility toward the judicious use of antibiotics, which can serve to eradicate antibiotic resistance.